Sport and education: tribute to Martin Lee - Manuel J. Coelho e Silva (Investigação, 2007)
This book has been produced as a tribute to the work of Martin Lee on the role of sport in the socio-moral education of young people. After conducting the first UK conference on Children in Sport, founded the Institute for the Study of Children in Sport at Bedford College of Higher Education in 1986 and created level 1, 2 and 3 courses on coaching children for the National Coaching Foundation. He also edited a book on Coaching Children in Sport. His course book on Coaching Children in Mini-basketball was produced for international distribution. The study of values has been central in Martin's research which also embraced such topics as self-concept, leadership, coaching behaviour, and parental influence. In a series of research commissions examined the literature, clarified measurement requirements, identified values activated in sport, and led an international project on fair play. He then ran a survey to show how values influence attitudes directly and through the mediation of achievement goals. Two new instruments arose from this research: the Attitudes to Moral Decision-making in Youth Sport Questionnaire and the Youth Sport Values Questionnaire-2. These will open up research into gamesmanship, by which competitors seek an unfair advantage without breaking the rules, and into the mechanisms by which moral, competence and status values guide behaviour and create value conflicts. I am also grateful to colleagues at the University of Coimbra for their initiative in gathering the distinguished international scholars who have contributed to this book. Their collective insights will enhance the understanding of socio-moral education through sport and lead to informed and sensitive policy development in both sport and education.